Two-directional synthesis as a tool for diversity-oriented synthesis: Synthesis of alkaloid scaffolds - O’Connell, Kieron M. G.; Díaz-Gavilán, Monica; Galloway, Warren R. J. D.; Spring, David R. (Beilstein Journal of Organic Chemistry, 2012)
Two-directional synthesis represents an ideal strategy for the rapid elaboration of simple starting materials and their subsequent transformation into complex molecular architectures. As such, it is becoming recognised as an enabling technology for diversity-oriented synthesis. Herein, we provide a thorough account of our work combining two-directional synthesis with diversity-oriented synthesis, with particular reference to the synthesis of polycyclic alkaloid scaffolds.
Keywords: alkaloids; cascade reactions; chemical diversity; diversity-oriented synthesis; Lewis acid catalysis; two-directional synthesis